Tinjauan Yuridis Tentang Penyelesaian Sengketa Illegal Logging Yang Dilakukan Oleh Masyarakat Adat Kasepuhan Ciptagelar - Sinurat, Natan; Sari, Legian; Simanjuntak, Frisky Agnes; Solahudin, Amir (CV. Publikasi Indonesia, 2023)
Indigenous peoples are a group of people in an area who have their own wealth and can manage their wealth independently. A traditional forest is a state forest that is in the area of ​​indigenous peoples which is managed and utilized by the indigenous peoples themselves. One example of the existence of indigenous peoples and traditional forests is Kasepuhan Ciptagelar in Sukabumi Regency, West Java. These people already have customary laws that they have used for generations. Among these customary laws, one of them regulates illegal logging activities. According to this customary law, someone who violates customary forest provisions will be given sanctions sequentially, from replanting as many as 1,000 tree seeds, to submitting laws to state law if the customary law given does not create a deterrent effect on the perpetrators.